STUDENTS’ DIFFICULTIES IN DESCRIBING PLACE AT SPEAKING CLASS: EXPLORING THE INFLUENCING FACTORS - Loly Novita; Puspa Gundary; Gusparia Gusparia (Ensiklopedia Education Review, 2022)
The objective of this research is to know the factors that influence the students’ difficulties in describing places based on internal and external factors. The subject of this research consists 24 students. The method used in this study was Descriptive Analysis. The data            of this research were gathered through quiz and interview questions. The techniques of data analysis used quantitative and qualitative analysis. The researcher obtained the score of the quiz result were 66,5%. It was categorized fair good. And the factor that influence the students’ difficulties based on indicator of speaking in observation checklist were students still embarrassed, lack of vocabulary and grammar, difficulties in pronouncing word and difficulties in developing ideas while speaking. The factors that influence the students’ difficulties comes from the internal factors and external factors. From internal factors were Readiness to learn which is 40%, interest and talent is 73%, physiological is 46% and intelligence is 88. From the external factors are teaching methods and curriculum. Teaching methods is 26% and curriculum is 31%.